Characterisation and diagnosis of ulcers in inpatient dermatology consultation services: A multi‐centre study. Issue 6 (2nd September 2019) - Haynes, Dylan; Hammer, Phoebe; Malachowski, Stephen J.; Kaffenberger, Benjamin; Yi, Jonathan S.; Vera, Nora; Calhoun, Cody; Shinohara, Michi M.; Seminario‐Vidal, Lucia; Trinidad, John C.; Keller, Jesse J.; Ortega‐Loayza, Alex G.
Abstract: Accurate and prompt diagnosis of skin ulcers is critical to optimise management; however, studies in hospitalised patients are limited. This retrospective review of dermatologic consultations included 272 inpatients with skin ulcers between July 2015 and July 2018 in four U.S. academic hospitals. The median age was 54 years and 45% were male. In 49.3% of the patients, skin ulcers were considered the primary reason for admission. Ulcers of 62% were chronic and 49.6% were located on the lower extremities. Pyoderma gangrenosum (17.3%), infection (12.5%), and exogenous causes (11.8%) were the leading aetiologies; 12% remained diagnostically inconclusive after consultation. Diagnostic agreements pre‐dermatology and post‐dermatology consult ranged from 0.104 (n = 77, 95% CI 0.051‐0.194) to 0.553 (n = 76, 95% CI 0.440‐0.659), indicating poor‐modest agreement. This study highlights the diagnostic complexity and relative incidences of skin ulcers in the inpatient setting.